Retail franchising - Doherty, Anne Marie (International journal of retail & distribution management, 2002)
Franchising has long been a popular mode of expansion for manufacturing firms and service sector companies, particularly those operating in the fast food restaurant business. However, in recent years retailing has become a major sector of franchise growth in advanced economies.